Unlocking Fun Learning: Gamification Training for Teachers at SD Inpres 1 Talise (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
The rapid development of digital technology in the twenty-first century demands innovation in the teaching and learning process. Teachers are required to design engaging, interactive, and meaningful learning experiences for students. This community service program aimed to enhance teachers’ understanding and skills in implementing gamification as a learning strategy. The activity consisted of training and mentoring sessions that introduced teachers to gamification concepts and the practical use of digital platforms such as Wordwall. The training was conducted on 7 August 2025 at SD Inpres 1 Talise, Palu, Central Sulawesi. The participants of this training were ten teachers. The data were collected through documentation and participant evaluation questionnaires. The results showed that the training was highly effective, with all evaluated aspects (material quality, facilitator performance, implementation, and impact) receiving “very good” ratings (average score 4.56). Teachers reported increased motivation, knowledge, and confidence in applying gamification in the classroom. This program demonstrates that gamification-based training can serve as an effective medium to foster teacher innovation and support the development of fun, student-centered learning environments aligned with 21st-century educational demands.